2000
DOI: 10.1021/jp9935283
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Dispersivity of Charge Transport and Holographic Response Time in an Organic Photorefractive Glass

Abstract: We report on photoelectric and holographic investigations of an organic photorefractive material based on a low molar mass glass with both photoconductive and nonlinear optical properties. By implementing a suitable plasticizer we obtained a composite system which shows extremely fast initial response times down to 450 µs at writing beam intensities of I write ) 10.8 W/cm 2 and 2.5 ms at the canonical intensity of I write ) 1 W/cm 2 . Furthermore, high refractive index modulations up to ∆n ) 6.1 × 10 -3 , long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The response time, initially 30 ms, [64] can be pushed down to 2.5 ms with the use of an optimized plasticizer and a high Dn of 6 Â 10 À3 was obtained. [65,66] Furthermore, shelf lifetimes of nearly two years have been reported. [65] Thus, low molecular weight glasses show promise for further development; nevertheless, systematic variations of the chromophore and the photoconductor require extensive synthetic efforts.…”
Section: Low Molecular Mass Glassesmentioning
confidence: 99%
See 2 more Smart Citations
“…The response time, initially 30 ms, [64] can be pushed down to 2.5 ms with the use of an optimized plasticizer and a high Dn of 6 Â 10 À3 was obtained. [65,66] Furthermore, shelf lifetimes of nearly two years have been reported. [65] Thus, low molecular weight glasses show promise for further development; nevertheless, systematic variations of the chromophore and the photoconductor require extensive synthetic efforts.…”
Section: Low Molecular Mass Glassesmentioning
confidence: 99%
“…Performance characteristics of organic photorefractive materials in terms of holographic speed t À1 and optical gain G at a power density of 1 W cm À2 . The systems are the amorphous glass DR1-DCTA [65] and the fastest liquid crystal reported so far. [77] The host ± guest systems depicted are PVK composites with the chromophores AODCST, [55] DMNPAA, [48] FTCN, [36] and PDCST, [37] a polyfluorene (TFB), [32] and TPDac.…”
Section: Qualitative Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zilker and co-workers have also shown that a more dispersive charge transport leads to a slower holographic response. 26 The doping of B6 with ferrocene also results in a decrease in steady-state amplitude of the diffracted beam. This evolution is shown in Fig.…”
Section: Photorefractive Propertiesmentioning
confidence: 99%
“…Additional HTOF investigations in an organic glass were performed in Ref. [37]. As mentioned above, for dispersive charge transport the relationship between the drift velocity measured by the time delay of the first peak in a non-oscillating HTOF trace and the actual distribution of mobilities is not a-priori clear.…”
Section: Review Of Mobility Investigations Performed Using Htofmentioning
confidence: 99%